Lenkijos ir Lietuvos unijos XX amžiaus lenkų istoriografija - Jučas, Mečislovas (Lietuvos istorijos studijos, 1998)
Lithuania and Poland lived together for four hundred years. Two states were joined by the state's organization, common ruler and parliament (from 1569), family ties, language and customs, intellectual life, Catholic religion, and Church's organization. Although Lithuania's position was not relevant to Poland, the king lived in Poland, the Polish nobility was predominant in parliamentary life, furthermore, the Polish culture was much richer. The Lithuania and Poland two-sided state model was not only unique but also constant, strong, and even attractive. That is why the Poland-Lithuania union survived for a long period, and it is worth international attention. But it still is a domain of Polish historiography, which seeks to give answers for all questions concerning the union's stages: Krėva treaty in 1385, union of Lublin in 1569, reforms in 1791, and the end of the union too.Historians had different opinions about the Krėva treaty's reasons. Some of them (A. Prochaska, F. Koneczny, H. Paszkiewicz, O. Halecki) emphasized the Polish nobility's attempts to rule Halič-Volyn territory, which was also desired by Hungary and Lithuania. Until 1370, Poland was looking for a union with Hungary against Lithuania, later with Lithuania against Hungary. As a consequence, the Krėva treaty was signed in 1385. Other historians (H. Łowmiański, J. Bardach, J. Ochmański) saw the growing threat of the Teutonic Order for Lithuania and late Christianization problems resulting in the union with Poland. This very opinion became an unquestionable truth. Jogaila's promise "terras suas ... Coronae regni Poloniae perpetuo applicare" made a ground for many debates. Historians separated. Some of them thought that it was Jogaila and Polish nobility's incorporational policy. A. Lewicki and his follower F. Koneczny developed this incorporational theory in 1893, and it was undertaken by the majority of Polish historians. But the disputes concerned only its duration: A. Lewicki, L. Kolankowski, H. Łowmiański spoke about 1446; S. Kutrzeba, O. Halecki about 1401; J. Bardach mentioned 1398, and F. Koneczny - 1392.Another group of Polish historians - H. Paszkiewicz, A. Vetulani, J. Adamus, and from 1937 O. Halecki - emphasized the dependence of the Grand Duke of Lithuania on the Polish king. There were no big debates on the reasons for the Lublin union: growing political activity of the Lithuanian nobility and its attempts to have equal rights with the Polish nobility, war between Lithuania and Moscow, and hope for the Polish nobility to realize old state rights, i.e., "executional attempt," and finally, the dominance and attractiveness of Polish culture.There were no arguments on the time when the union became not just a kingdom but real - parliamentary. It happened in 1569. But it was not clear whether this union proclaimed a unitarian state of Poland and the failure of the Lithuanian state or created a federation of two states. O. Balcer, W. Konopczyński, S. Kościałkowski, K. Chodynicki, and H. Łowmiański saw it as the end of the Lithuanian state. S. Kutrzeba, O. Halecki, L. Kolankowski, and J. Bardach saw a merging of two states and two nations.Specialists of the Enlightenment were seeking features of Lithuanian statehood even in the 18th century. They found functions of Lithuanian statehood, at first the existence of the separate state institutions: chancellor, marshal, treasury, and army; also law, court system, Lithuanian parliamentarism. They considered, however, the reforms of the end of the 17th century as an abolishment of Lithuanian statehood. The "Bilateral Obligation" signed on October 20th, 1791, acknowledged the central offices to be in Warsaw, giving Lithuanians only participants' status. It still was the Polish compromise on the union's question. But it never came into being. The existence of the Poland-Lithuania state and also the union was coming to an end.